Mechanistic insights into hormesis induced by erythromycin in the marine alga Thalassiosira weissflogii - Jiezhang Mo; Runnan Lv; Xian Qin; Xintong Wu; Haibo Chen; Neng Yan; Jingchun Shi; Yinglin Wu; Wenhua Liu; Richard Y.C. Kong; Jiahua Guo (Ecotoxicology and Environmental Safety, 2023)
Erythromycin (ERY) is a typical macrolide antibiotic with large production and extensive use on a global scale. Detection of ERY in both freshwaters and coaster seawaters, as well as relatively high ecotoxicity of ERY have been documented. Notably, hormesis has been reported on several freshwater algae under ERY stress, where growth was promoted at relatively lower exposures but inhibited at higher treatment levels. On the contrary, there is limited information of ERY toxicity in marine algae, hampering the risk assessment on ERY in the coaster waters. The presence of hormesis may challenge the current concept of dose-response adopted in chemical risk assessment. Whether and how exposure to ERY can induce dose-dependent toxicity in marine algae remain virtually unknown, especially at environmentally relevant concentrations. The present study used a model marine diatom Thalassiosira weissflogii (T. weissflogii) to reveal its toxicological responses to ERY at different biological levels and decipher the underlying mechanisms. Assessment of multiple apical endpoints shows an evident growth promotion following ERY exposure at an environmentally relevant concentration (1 µg/L), associated with increased contents reactive oxygen species (ROS) and chlorophyll-a (Chl-a), activated signaling pathways related to ribosome biosynthesis and translation, and production of total soluble protein. By contrast, growth inhibition in the 750 and 2500 µg/L treatments was attributed to reduced viability, increased ROS formation, reduced content of total soluble protein, inhibited photosynthesis, and perturbed signaling pathways involved in xenobiotic metabolism, ribosome, metabolism of amino acid, and nitrogen metabolism. Measurements of multiple apical endpoints coupled with de novo transcriptomics analysis applied in the present study, a systems biology approach, can generate detailed mechanistic information of chemical toxicity including dose-response and species sensitivity difference used in environmental risk assessment.